Approaching 23% with large‐area monoPoly cells using screen‐printed and fired rear passivating contacts fabricated by inline PECVD. (12th December 2018) - Nandakumar, Naomi; Rodriguez, John; Kluge, Thomas; Groβe, Thomas; Fondop, Lauretta; Padhamnath, Pradeep; Balaji, Nagarajan; König, Marcel; Duttagupta, Shubham
Abstract: We present n ‐type bifacial solar cells with a rear interfacial SiOx / n + :poly‐Si passivating contact ('monoPoly' cells) where the interfacial oxide and n + :poly‐Si layers are fabricated using an industrial inline plasma‐enhanced chemical vapor deposition (PECVD) tool. We demonstrate outstanding passivation quality with dark saturation current density ( J 0 ) values of approximately 3 fA/cm 2 and implied open‐circuit voltage ( iV oc ) of 730 mV at 1‐sun conditions after firing in an industrial belt furnace. Using a simple solar cell process flow that can be easily adapted for mass production, a peak cell efficiency of 22.8% with a cell open circuit voltage ( V oc ) of 696 mV is achieved on large‐area, screen‐printed, Czochralski‐silicon ( Cz‐ Si) solar cells using commercial fire‐through metal pastes. Abstract : We present n ‐type bifacial solar cells with an interfacial SiOx / n + :poly‐Si passivated rear contact where the interfacial oxide and n + :poly‐Si layers are fabricated using an industrial inline plasma‐enhanced chemical vapor deposition (PECVD) tool. Using a simple solar cell process flow that can be easily adapted for mass production, a peak cell efficiency of 22.8% with a cell open circuit voltage ( V oc ) of 696 mV is achieved on large‐area, screen‐printed, Czochralski‐silicon ( Cz‐ Si) solar cells using commercial fire‐through metal pastes.